The relationship between knee muscles isokinetic strength and dynamic balance performance in volleyball players - Aka, H.; Altundag, E. (International Journal of Applied Exercise Physiology, 2020)
The objective of the study is to investigate the relation between isokinetic knee strength and dynamic balance performance. 12 elite female volleyball players participated in the study voluntarily. The dominant and nondominant isokinetic leg strength, concentric extension and flexion of the participants were determined by means of an isokinetic dynamometer with the speed of 60°/s, and the dynamic balance performance by isokinetic balance system. Spearman correlation analysis was used to determine the relation between isokinetic leg strength and dynamic balance performance. As a result of the analysis, a negative significant relation was found between 60°/s angular speed quadriceps and hamstring muscle strengths and dynamic balance performance (p<0.05). In consequence of this study, it was determined that the increase in lower extremity isokinetic strength improved balance performance significantly. It is considered that this result can be an important factor in decreasing the risk of injuries in athletes and preventing performance losses. It can be stated that athletes should practice exercises improving the isokinetic strength of knee circumference muscles in order to increase dynamic balance performance that is one of the important factors in physical fitness parameters` performance in all branches of sports.